2017
DOI: 10.15644/asc51/3/4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Shaping Ability of 10 Rotary and Reciprocating Systems: an In Vitro Study with AutoCAD

Abstract: ObjectiveThe aim of this study was to compare the cutting are, root canal anatomy preservation and non-instrumented areas of F360®, F6-SkyTaper®, Hyflex-EDM®, iRACE®, Neoniti®, O.Shape®, P.Next®, Reciproc®, Revo-S® and Wave-One-Gold® size 25 files.Materials and Methods300 teeth with a single straight root and a circular or elliptical root canal were divided into 10 groups (1-F360®, 2- F6-SkyTaper®, 3-Hyflex-EDM®, 4-iRACE®, 5-Neoniti®, 6-O.Shape®, 7-P.Next®, 8-Reciproc®, 9-Revo-S® and 10-Wave-One-Gold®) cut int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“…Both the file systems showed some degree of canal transportation, especially in the apical third. [1819]…”
Section: Discussionmentioning
confidence: 99%
“…Both the file systems showed some degree of canal transportation, especially in the apical third. [1819]…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that F6 SkyTaper files were capable of removing 694.0±0.02 mm2 of dentin, but the dentin removal rate was 0.604±0.66 mm2 for One Shape files. (23) Based on the results of this research, the dentin removal rate was higher for F6 SkyTaper files although there were no statistically significant differences (P<0.05). The results of the mentioned study were similar to the results of the present study.…”
Section: Discussionmentioning
confidence: 67%
“…Rubio et al performed a study to determine the rate of root canal preparations of 10 types of rotary files. (23) They compared the images before and after the preparation of the samples using the AutoCAD software. The results showed that F6 SkyTaper files were capable of removing 694.0±0.02 mm2 of dentin, but the dentin removal rate was 0.604±0.66 mm2 for One Shape files.…”
Section: Discussionmentioning
confidence: 99%
“…2017 have compared the remaining dentin thickness following instrumentation, however, no study has been attempted to compare remaining dentin thickness in two dimensions – mesiodistal and buccolingual direction. [ 13 14 15 16 ] Hence, the present study focused on measuring the dentin removed in both mesiodistal and buccolingual direction.…”
Section: Discussionmentioning
confidence: 99%